High PV Penetration Impact on European-based LV Residential Network - Kyairul Azmi Baharin; Nur Aliah Isa; Chin Kim Gan; Meysam Shamshiri (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
The impact of high PV penetration into the grid particularly at the distribution side has been extensively studied. However, most of the available research focuses on North American style systems. This project aims to investigate the effect of high PV penetration at a residential area in a European-based distribution network, which is electricity supply system Malaysia is based on. The modeling is done using OpenDSS while the network model used is the IEEE European Low Voltage Test Feeder which consists of 55 loads representing a generic housing area. Each load point is then equipped with a 4 kW PV system-representing a typical size for a house installation. PV output variability is then introduced into the modeling using two sample days of actual irradiance variability obtained from UTeM Malaysia; one for clear day and another for a high variability day. Voltage unbalance, voltage rise and reverse power flow were analyzed. One significant finding of this project is that voltage rise exceeds the standard of 1.05 pu during noon. Besides that, the high variability days significantly affect the mitigation measures required to manage reverse power flow.